SISTEM PENYIMPANAN BAHAN BAKU PASTRY DI NONGSA POINT MARINA & RESORT BATAM - Sapitri, Awidiya; Sidiq, Siti Sofro (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
Currently the industry is related to tourism services such as transportation businesses, accommodation (hotels, guest houses and others). The Riau Islands, especially Batam City, have valuable assets and potential and have their own characteristics that must be developed, managed and promoted to attract tourists. Nongsa Point Marina & Resort Batam is a four-star hotel in the city of Batam. Its strategic location is on Jl. Hang Lekiu, Sambau, District. Nongsa, Batam City, Riau Islands. Among the small islands of Indonesia and also close to Singapore and Malaysia. This can be an attractive factor for tourists at home and abroad. A hotel certainly has many facilities, one of which is pastry. Nongsa Point Marina & Resot Batam is one of the hotels that has its own pastry. It can be said that pastry is a type of processed dessert which is a combination of ingredients that have a sweet taste and contain fat which is then baked and then served with drinks such as tea and coffee. This research aims to determine the storage system for raw materials in the pastry section of Nongsa Point Marina & Resort Batam. In order for the storage system to run well, several procedures must be carried out which are required for storing raw materials. Food ingredients are divided into 2, namely Goceries ingredients and Perishable ingredients. The storage of these two ingredients must be carried out continuously starting from the type of storage space and equipment, storage arrangement, storage location, safety storage and labeling of food ingredients until the ingredients are ready to be processed to obtain good quality ingredients. This research uses qualitative research methods and to obtain data the author uses interviews, observation and documentation. From the results of research conducted by the author for 4 months at Nongsa Point Marina & Batam Resort, it was found that the storage system was in good condition but did not comply with the correct storage procedures. Keywords: Nongsa Point Marina & Resort Batam, Wholesale, Perishable, Storage System.